Photovoltaic front silver paste and preparation method thereof
By using spherical silver powder, specific glass powder and MXene nanosheets in the photovoltaic front silver paste, the problem of contact difficulties of N-TOPCon photovoltaic cells is solved, and silver paste with high conductivity and stability is achieved, which significantly improves the photoelectric conversion efficiency and stability of the battery.
Patent Information
- Application Number
- CN202411962210.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
N-TOPCon photovoltaic cells have difficulties in contact, and traditional silver paste cannot meet their contact needs, resulting in limited conductivity and affecting the photoelectric conversion efficiency and stability of the battery.
Spherical silver powder, specific glass powder and MXene nanosheets are used as the main raw materials, and a high-conductivity photovoltaic frontal silver paste is prepared through specific ratios and process treatments. The silver paste optimizes the dispersion and contactability of the silver powder and the glass powder by adjusting the glass transition temperature and dosage of the glass powder, and improves the contact effect between the electrode and the silicon matrix.
It significantly reduces contact resistance, improves current collection efficiency and photoelectric conversion efficiency, and enhances the stability and performance of solar cells.
Smart Images

Figure CN119763892A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive silver paste, and in particular to a photovoltaic front silver paste and a preparation method thereof. Background Art
[0002] Silicon materials are currently considered an ideal choice for the development of crystalline silicon solar cells due to their excellent performance. Among the many types of photovoltaic cells, N-TOPCon photovoltaic cells are becoming the mainstream technology of photovoltaic cells due to their excellent photoelectric conversion efficiency, low temperature coefficient and double-sided electrical characteristics. However, N-TOPCon photovoltaic cells currently have the problem of difficult contact, and traditional silver paste cannot meet the contact requirements.
[0003] Traditional photovoltaic front silver paste is mainly composed of a mixture of silver powder, glass powder and organic carrier. Although silver is a metal with excellent conductivity, in actual application, the conductivity of silver paste is still restricted by many factors, such as the particle size, shape and dispersion of silver powder. These factors limit the further improvement of the conductivity of silver paste, thereby affecting the contact effect of N-TOPCon photovoltaic cells. Therefore, finding new materials that can solve the contact problem of N-TOPCon photovoltaic cells or improving the formula of existing silver paste has become the focus of current research.
[0004] Chinese patent CN117766195A provides a method for preparing photovoltaic front silver paste. In the process of pre-dispersing the organic carrier and the glass powder, the surface activity of the glass powder can be adjusted by coating the glass powder in advance with the surfactant in the organic carrier. The long-chain resin can give the glass powder a dispersed skeleton. The combined effect of the dispersant and the long-chain resin can also avoid the agglomeration and sedimentation of the glass powder. The above-mentioned pre-dispersion process can generally help improve the wettability of the glass powder surface and the organic carrier, thereby improving the dispersibility of the glass powder and optimizing the fineness of the final front silver paste. However, photovoltaic front silver paste has problems such as low photoelectric conversion efficiency and insufficient contact. Summary of the invention
[0005] In order to solve the problems in the prior art, the first aspect of the present invention provides a photovoltaic front silver paste. The preparation raw materials include, by weight: 85-90 parts of spherical silver powder, 2-3 parts of glass powder, 0.1-1 parts of MXene nanosheets, and 8-9 parts of organic carriers; the glass powder includes a first glass powder and a second glass powder.
[0006] In one embodiment, the particle size D50 of the spherical silver powder is 0.6-2 μm.
[0007] In a preferred embodiment, the particle size D50 of the spherical silver powder is 1.2-1.7 μm, which can be 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm. More preferably, the particle size D50 of the spherical silver powder is 1.5 μm.
[0008] In one embodiment, the glass transition temperature of the first glass frit is higher than the glass transition temperature of the second glass frit.
[0009] In one embodiment, the glass transition temperature of the first glass powder is 350-380°C, and can be 350°C, 360°C, 370°C, or 380°C.
[0010] In a preferred embodiment, the glass transition temperature of the first glass powder is 360°C.
[0011] In one embodiment, the glass transition temperature of the second glass powder is 300-330°C, and may be 300°C, 310°C, 320°C, or 330°C.
[0012] In a preferred embodiment, the glass transition temperature of the second glass powder is 320°C.
[0013] In one embodiment, the mass ratio of the first glass powder to the second glass powder is (3-5):(5-6), which can be 3:5, 1:2, 4:5, 1:1, 2:3, 5:6.
[0014] In a preferred embodiment, the mass ratio of the first glass powder to the first glass powder is 2:3.
[0015] After a lot of creative research, the applicant found that in the system of the present invention, when the glass transition temperature of the second glass powder is lower than the glass transition temperature of the first glass powder, and the mass ratio of the first glass powder to the second glass powder is (3-5): (5-6), the contact resistance can be reduced, the current collection efficiency can be improved, and the conversion efficiency and stability can be improved. The possible reason is that the second glass powder has a certain activity under low-temperature sintering, which can achieve the etching of the anti-reflection layer. This enables the electrode to better contact with the silicon substrate, reduce the contact resistance, and improve the current collection efficiency. At higher temperatures, due to the high viscosity of the first glass powder, it can affect and reduce the fluidity of the first glass powder, and further slow down the corrosion rate of the first glass powder, so that it will not cause excessive corrosion to the silicon substrate while etching the anti-reflection layer, slowing down the possibility of the second glass powder penetrating the anti-reflection layer to corrode the silicon substrate, which helps to reduce the leakage risk of the solar cell and improve its conversion efficiency and stability.
[0016] In one embodiment, the particle size D50 of the first glass powder and the second glass powder is 0.5-3 μm.
[0017] In one embodiment, the particle size D50 of the first glass powder and the second glass powder is 1.3-1.5 μm.
[0018] Examples include 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, and 3 μm.
[0019] In one embodiment, the raw materials for preparing the first glass powder include, by weight: 20-24 parts of SiO2, 28-32 parts of PbO, 15-16 parts of B2O3, 13-15 parts of Al2O3, and 15-16 parts of ZnO.
[0020] In a preferred embodiment, the raw materials for preparing the first glass powder include, by weight: 23 parts of SiO2, 30 parts of PbO, 16 parts of B2O3, 14 parts of Al2O3, and 16 parts of ZnO.
[0021] In one embodiment, the preparation method of the first glass powder comprises the following steps: mixing SiO2, PbO, B2O3, Al2O3 and ZnO, melting at high temperature, quenching and screening to obtain the first glass powder.
[0022] In one embodiment, the raw materials for preparing the second glass powder include, by weight: 15-17 parts of SiO2, 35-38 parts of PbO, 11-12 parts of B2O3, 9-10 parts of Al2O3, 17-18 parts of ZnO, and 1-4 parts of Na2O.
[0023] In a preferred embodiment, the raw materials for preparing the second glass powder include, by weight: 16 parts of SiO2, 38 parts of PbO, 11 parts of B2O3, 9 parts of Al2O3, 17 parts of ZnO, and 3 parts of Na2O.
[0024] In one embodiment, the preparation method of the second glass powder comprises the following steps: mixing SiO2, PbO, B2O3, Al2O3, ZnO and Na2O, melting at high temperature, quenching and screening to obtain the second glass powder.
[0025] In one embodiment, the high temperature melting temperature is 1100-1400°C, which can be 1100°C, 1200°C, 1300°C, 1400°C.
[0026] In one embodiment, the method for preparing the MXene nanosheets comprises at least the following steps:
[0027] (1) Stir concentrated hydrochloric acid, lithium fluoride and Ti3AlC2 for 30-40 hours, centrifuge for 3-5 times and take the supernatant;
[0028] (2) ultrasonicating the supernatant at a power of 300-400 W for 2-3 h, centrifuging and taking the upper colloidal solution;
[0029] (3) freeze-drying the upper colloidal solution for 30-40 hours to obtain the product.
[0030] The concentrated hydrochloric acid described in the present application is hydrochloric acid with a mass fraction of hydrogen chloride of 36-38%.
[0031] In one embodiment, the step (2) is specifically as follows: ultrasonicating the supernatant at 300-400 W for 2-3 h, centrifuging at 3500-4000 rpm for 1-1.5 h to obtain an upper layer solution, and centrifuging the upper layer solution at 6000-7000 rpm to obtain an upper colloidal solution.
[0032] In a preferred embodiment, the preparation method of the MXene nanosheet is specifically as follows:
[0033] (1) After stirring concentrated hydrochloric acid and lithium fluoride for 5 minutes, Ti3AlC2 was added, stirred at 36°C for 36 hours, washed with deionized water, and centrifuged 4 times to obtain a supernatant; the pH value of the supernatant was 6;
[0034] (2) the supernatant was ultrasonicated at 300 W for 2 h, centrifuged at 3500 rpm for 1 h to obtain the upper solution, and the upper solution was centrifuged at 6500 rpm to obtain the upper colloidal solution;
[0035] (3) Freeze the upper colloidal solution for 6 hours and then put it into a freeze dryer for freeze drying for 30 hours to obtain the product.
[0036] In one embodiment, the raw materials for preparing the organic carrier include: 0.7-2 parts of resin, 0.5-1 parts of dispersant, 0.05-0.2 parts of thixotropic agent, 0.3-0.5 parts of silicone oil, and 5.6-7 parts of solvent.
[0037] In a preferred embodiment, the raw materials for preparing the organic carrier include: 1.1 parts of resin, 0.7 parts of dispersant, 0.1 parts of thixotropic agent, 0.4 parts of silicone oil, and 6.4 parts of solvent.
[0038] In one embodiment, the resin includes at least one of styrene block copolymer and polyvinyl acetal.
[0039] In a preferred embodiment, the resin includes styrene block copolymer and polyvinyl acetal.
[0040] In one embodiment, the styrene block copolymer includes at least one of a styrene-ethylene-propylene-styrene block copolymer, a styrene-isoprene-styrene block copolymer, and a styrene-butadiene-styrene block copolymer.
[0041] In a preferred embodiment, the styrene block copolymer is a styrene-ethylene-propylene-styrene block copolymer.
[0042] In a more preferred embodiment, the brand of the styrene-ethylene-propylene-styrene block copolymer is G1701, which is purchased from Kraton Polymers Corporation of the United States.
[0043] In one embodiment, the polyvinyl acetal includes at least one of polyvinyl formal, polyvinyl acetal, and polyvinyl butyral.
[0044] In a preferred embodiment, the polyvinyl acetal is polyvinyl butyral.
[0045] In a more preferred embodiment, the brand of polyvinyl butyral is B60HH, purchased from Kuraray Co., Ltd. of Japan.
[0046] In one embodiment, the mass ratio of the styrene-ethylene-propylene-styrene block copolymer to polyvinyl butyral is (6-13):(1-3), which can be 13:1, 6:1, 9:2, 3:1, 2:1, or 13:3.
[0047] In one embodiment, the dispersant comprises sodium dodecylbenzene sulfonate.
[0048] In one embodiment, the thixotropic agent includes at least one of sodium polyamide, polyamide wax, and polyhydroxystearic acid.
[0049] In a preferred embodiment, the thixotropic agent is sodium polyamide.
[0050] In one embodiment, the silicone oil is a low viscosity silicone oil.
[0051] In a preferred embodiment, the viscosity of the low-viscosity silicone oil at 25° C. is 50 cst.
[0052] In one embodiment, the solvent includes at least one of diethylene glycol butyl ether acetate, benzyl benzoate, and alcohol ester dodecahydrate.
[0053] In a preferred embodiment, the solvent includes diethylene glycol butyl ether acetate, benzyl benzoate and alcohol ester dodecaned.
[0054] In one embodiment, the mass ratio of diethylene glycol butyl ether acetate, benzyl benzoate and alcohol ester is (2.2-2.6):(2.4-2.9):(1-1.4), which can be 2.2:2.4:1, 2.5:2.7:1.2, 2.6:2.9:1.4.
[0055] In one embodiment, the method for preparing the organic carrier comprises the following steps: dissolving the resin, dispersant, thixotropic agent, silicone oil and solvent, mixing and stirring the mixture to obtain the organic carrier.
[0056] A second aspect of the present invention provides a method for preparing photovoltaic front silver paste, comprising at least the following steps:
[0057] The MXene nanosheets are added to the organic carrier and ultrasonically dispersed at room temperature to obtain a MXene dispersion;
[0058] Glass powder and spherical silver powder are added to the MXene dispersion and stirred evenly at room temperature to obtain a slurry, and the slurry is dispersed 5-7 times by a three-roll mill.
[0059] In one embodiment, the ultrasonic dispersion power is 300-400 W, and the ultrasonic time is 10-20 min.
[0060] In a preferred embodiment, the power of the ultrasonic dispersion is 300 W and the ultrasonic time is 10 min.
[0061] In one embodiment, the dispersion requirement is specifically that the slurry needs to be rolled at least twice for each dispersion.
[0062] Beneficial Effects
[0063] 1. The present invention introduces MXene nanosheets into the photovoltaic front silver paste. The preparation method is simple and easy to operate. By premixing with a specific organic carrier, the paste can have higher thixotropy at a lower viscosity. At the same time, MXene has high conductivity, good flexibility and stability, which can significantly improve the conductivity and stability of the silver paste.
[0064] 2. Specific resins and solvents are selected in the organic carrier of the present invention to ensure stable interaction with silver powder and MXene nanosheets without chemical reaction or phase separation.
[0065] 3. The present invention selects two glass powders with different glass transition temperatures and controls the mass ratio of the first glass powder to the second glass powder to be (3-5):(5-6), so that the electrode can better contact with the silicon substrate, reduce contact resistance, and improve current collection efficiency; at the same time, it helps to reduce the leakage risk of solar cells and improve their conversion efficiency and stability.
[0066] 4. The present invention uses a sheet-like structured MXene nanosheet prepared by a specific process to further increase the contact area between the silver powder and the organic carrier, and improve the integrity and efficiency of the conductive network; at the same time, the MXene nanosheet can fill the gaps between the silver particles, promote the close arrangement of the silver particles, and thus improve the compactness of the silver film layer. In addition, the MXene surface has rich functional groups that can chemically adsorb with the surface of the silver particles, enhancing the binding force between the MXene and the silver particles. This strong binding force helps to maintain close contact between the silver particles and improve the photoelectric conversion efficiency and performance stability of the photovoltaic cell.
[0067] 5. The present invention controls the amount of spherical silver powder, glass powder and MXene nanosheets to ensure uniform dispersion of each component, and promotes the full mixing of silver powder, MXene nanosheets and organic carriers to improve the photoelectric conversion efficiency of silver paste. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 This is the SEM image of the MXene nanosheets produced during the preparation process of Example 1. DETAILED DESCRIPTION
[0069] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the examples and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The experimental methods for which specific conditions are not specified in the examples are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be purchased commercially.
[0070] Example 1
[0071] In a first aspect, the present embodiment provides a photovoltaic front silver paste. The raw materials for its preparation include, by weight: 87.9 parts of spherical silver powder, 3 parts of glass powder, 0.3 parts of MXene nanosheets, and 8.8 parts of organic carriers; the glass powder includes a first glass powder and a second glass powder.
[0072] The particle size D50 of the spherical silver powder is 1.5 μm.
[0073] The glass transition temperature of the first glass powder is 360°C.
[0074] The glass transition temperature of the second glass powder is 320°C.
[0075] The mass ratio of the first glass powder to the second glass powder is 2:3.
[0076] The particle size D50 of the first glass powder and the second glass powder is 1.3-1.5 μm.
[0077] The preparation method of the first glass powder comprises the following steps: mixing 23 parts of SiO2, 30 parts of PbO, 16 parts of B2O3, 14 parts of Al2O3 and 16 parts of ZnO by mass, melting at 1300°C, quenching and sieving to obtain the first glass powder.
[0078] The preparation method of the second glass powder comprises the following steps: mixing 16 parts of SiO2, 38 parts of PbO, 11 parts of B2O3, 9 parts of Al2O3, 17 parts of ZnO and 3 parts of Na2O by mass, melting at 1300°C, quenching and sieving to obtain the second glass powder.
[0079] The preparation method of the MXene nanosheet is specifically as follows:
[0080] (1) 6 mL of hydrochloric acid with a mass fraction of 37% hydrogen chloride was stirred with 0.3 g of lithium fluoride for 5 min, and then 0.3 g of Ti3AlC2 was added, stirred at 36° C. for 36 h, and then washed with deionized water, and centrifuged 4 times to obtain a supernatant; the pH value of the supernatant was 6;
[0081] (2) the supernatant was ultrasonicated at 300 W for 2 h, centrifuged at 3500 rpm for 1 h to obtain the upper solution, and the upper solution was centrifuged at 6500 rpm to obtain the upper colloidal solution;
[0082] (3) Freeze the upper colloidal solution for 6 hours and then put it into a freeze dryer for freeze drying for 30 hours to obtain the product.
[0083] The preparation method of the organic carrier comprises the following steps: according to weight percentage, 1.1 parts of resin, 0.7 parts of dispersant, 0.1 parts of thixotropic agent, 0.4 parts of silicone oil and 6.4 parts of solvent are dissolved, mixed and stirred evenly to obtain the organic carrier.
[0084] The resins are styrene-ethylene-propylene-styrene block copolymer and polyvinyl butyral.
[0085] The mass ratio of the styrene-ethylene-propylene-styrene block copolymer to polyvinyl butyral is 9:2.
[0086] The brand of the styrene-ethylene-propylene-styrene block copolymer is G1701, which is purchased from Kraton Polymers Company, USA.
[0087] The brand of the polyvinyl butyral is B60HH, purchased from Kuraray Co., Ltd. of Japan.
[0088] The dispersant is sodium dodecylbenzene sulfonate.
[0089] The thixotropic agent is sodium polyamide.
[0090] The silicone oil is low-viscosity silicone oil, and the viscosity of the low-viscosity silicone oil at 25° C. is 50 cst.
[0091] The solvents include diethylene glycol butyl ether acetate, benzyl benzoate and alcohol ester dodecahydrate.
[0092] The mass ratio of diethylene glycol butyl ether acetate, benzyl benzoate and alcohol ester dodecaned is 2.5:2.7:1.2.
[0093] A second aspect of the present embodiment provides a method for preparing photovoltaic front silver paste, comprising the following steps:
[0094] The MXene nanosheets were added to the organic carrier at room temperature and ultrasonically dispersed at 300 W for 10 min to obtain a MXene dispersion.
[0095] Glass powder and spherical silver powder are added to the MXene dispersion and stirred at room temperature to obtain a slurry. The slurry is dispersed 6 times by a three-roller mill, and the slurry needs to be rolled at least twice each time.
[0096] Figure 1 This is the SEM image of the MXene nanosheets produced during the preparation process of Example 1.
[0097] Example 2
[0098] The specific implementation of this embodiment is the same as that of Example 1, except that the first aspect of this embodiment provides a photovoltaic front silver paste, and the preparation raw materials include, by weight: 88.4 parts of spherical silver powder, 2.7 parts of glass powder, 0.1 parts of MXene nanosheets, and 8.8 parts of organic carriers; the glass powder includes a first glass powder and a second glass powder.
[0099] The mass ratio of the first glass powder to the second glass powder is 1:2.
[0100] Example 3
[0101] The specific implementation of this embodiment is the same as that of Example 1, except that the first aspect of this embodiment provides a photovoltaic front silver paste, and the preparation raw materials include, by weight: 88.2 parts of spherical silver powder, 2.7 parts of glass powder, 0.3 parts of MXene nanosheets, and 8.8 parts of organic carriers; the glass powder includes a first glass powder and a second glass powder.
[0102] The mass ratio of the first glass powder to the second glass powder is 1:2.
[0103] Example 4
[0104] The specific implementation of this embodiment is the same as that of Example 1, except that the first aspect of this embodiment provides a photovoltaic front silver paste, and the preparation raw materials include, by weight: 88 parts of spherical silver powder, 2.7 parts of glass powder, 0.5 parts of MXene nanosheets, and 8.8 parts of organic carriers; the glass powder includes a first glass powder and a second glass powder.
[0105] The mass ratio of the first glass powder to the second glass powder is 1:2.
[0106] Example 5
[0107] The specific implementation of this embodiment is the same as that of Embodiment 1, except that the mass ratio of the first glass powder to the second glass powder is 1:1.
[0108] Example 6
[0109] The specific implementation of this embodiment is the same as that of Example 1, except that the first aspect of this embodiment provides a photovoltaic front silver paste, and the preparation raw materials include, by weight: 88.2 parts of spherical silver powder, 2.7 parts of glass powder, 0.3 parts of MXene nanosheets, and 8.8 parts of organic carriers; the glass powder includes a first glass powder and a second glass powder.
[0110] The mass ratio of the first glass powder to the second glass powder is 4:5.
[0111] Performance Testing
[0112] The photovoltaic front silver paste prepared in each embodiment and the commercially available sample photovoltaic front silver paste were printed on N-type solar cells and sintered at 740° C., and then the IV electrical properties were tested using a Halm tester. The commercially available sample does not contain the MXene nanosheets in this application, the organic carrier raw material does not contain the dispersant sodium dodecylbenzene sulfonate, and the first glass powder raw material does not contain ZnO.
[0113] The test results are shown in Table 1.
[0114] It can be seen from Table 1 that the photoelectric conversion efficiency of Examples 1-6 is higher than that of commercially available photovoltaic front silver pastes, and the series resistance is lower than that of commercially available products. Among them, the photovoltaic front silver paste prepared in Example 1 has lower contact resistance, high open circuit voltage and fill factor, and at the same time brings an excellent aspect ratio and has extremely high conversion efficiency.
[0115] Table 1
[0116] sample Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Commercially available samples Eta / % 26.257 26.211 26.234 26.197 26.174 26.163 26.048 Voc / V 0.7344 0.7339 0.7342 0.7335 0.7320 0.7334 0.7331 Isc / A 13.9589 13.9525 13.9549 13.9560 13.9505 13.9478 13.9491 Rs / mOhm 1.31553 1.37753 1.35525 1.37697 1.38350 1.38214 1.39457 Rsh / Ohm 1802 1738 1784 1807 1809 1731 1651 FF / % 85.315 85.237 85.278 85.242 85.266 85.257 85.141 Irev2 / A 0.0330 0.0367 0.0344 0.0378 0.0398 0.0436 0.0445 H(μm) 7.92 7.36 7.79 7.56 8.16 7.54 7.49 W(μm) 19.3 19.31 19.45 19.21 20.35 19.24 19.88 H / W(%) 41.04 38.11 40.05 39.35 40.10 39.19 37.68
Claims
1. A photovoltaic front silver paste, characterized in that: The raw materials include, by weight: 85-90 parts of spherical silver powder, 2-3 parts of glass powder, 0.1-1 parts of MXene nanosheets, and 8-9 parts of organic carriers; the glass powder includes a first glass powder and a second glass powder.
2. The photovoltaic front silver paste according to claim 1, characterized in that: The glass transition temperature of the first glass frit is higher than the glass transition temperature of the second glass frit.
3. The photovoltaic front silver paste according to claim 2, characterized in that: The mass ratio of the first glass powder to the second glass powder is (3-5):(5-6).
4. The photovoltaic front silver paste according to claim 2 or 3, characterized in that: Calculated by weight, the raw materials for preparing the first glass powder include: 20-24 parts of SiO2, 28-32 parts of PbO, 15-16 parts of B2O3, 13-15 parts of Al2O3, and 15-16 parts of ZnO.
5. The photovoltaic front silver paste according to claim 2 or 3, characterized in that: Calculated by weight, the raw materials for preparing the second glass powder include: 15-17 parts of SiO2, 35-38 parts of PbO, 11-12 parts of B2O3, 9-10 parts of Al2O3, 17-18 parts of ZnO, and 1-4 parts of Na2O.
6. The photovoltaic front silver paste according to claim 1, characterized in that: The method for preparing the MXene nanosheets comprises at least the following steps: (1) Stir concentrated hydrochloric acid, lithium fluoride and Ti3AlC2 for 30-40 hours, centrifuge for 3-5 times and take the supernatant; (2) ultrasonicating the supernatant at a power of 300-400 W for 2-3 h, centrifuging and taking the upper colloidal solution; (3) freeze-drying the upper colloidal solution for 30-40 hours to obtain the product.
7. The photovoltaic front silver paste according to claim 6, characterized in that: The step (2) specifically comprises: subjecting the supernatant to ultrasonic treatment at a power of 300-400 W for 2-3 h, centrifuging at 3500-4000 rpm for 1-1.5 h to obtain an upper layer solution, and centrifuging the upper layer solution at 6000-7000 rpm to obtain an upper layer colloidal solution.
8. The photovoltaic front silver paste according to claim 1, characterized in that: The raw materials for preparing the organic carrier include, by weight: 0.7-2 parts of resin, 0.5-1 parts of dispersant, 0.05-0.2 parts of thixotropic agent, 0.3-0.5 parts of silicone oil, and 5.6-7 parts of solvent.
9. The photovoltaic front silver paste according to claim 8, characterized in that: The resin includes at least one of styrene block copolymer and polyvinyl acetal.
10. A method for preparing photovoltaic front silver paste according to any one of claims 1 to 9, characterized in that: At least the following steps are included: The MXene nanosheets are added to the organic carrier and ultrasonically dispersed at room temperature to obtain a MXene dispersion; Glass powder and spherical silver powder are added to the MXene dispersion and stirred evenly at room temperature to obtain a slurry, and the slurry is dispersed 5-7 times by a three-roll mill.
Citation Information
Patent Citations
Photovoltaic front silver paste and preparation method thereof
CN117766195A
Electrode slurry and photovoltaic cell
CN117524540A
MXene-SILVER CONDUCTIVE PASTE, ELECTRODE, AND METHOD
WO2023026188A1
Cited By
Solder-resistant conductive silver paste for PTC (Positive Temperature Coefficient) thermistor as well as preparation method and application thereof
CN121439311A
Low-temperature fast-curing silver paste for FPC antenna and preparation method of low-temperature fast-curing silver paste
CN121687613A